Application of relay puncture technique in treating patients with complicated lower extremity arterial diseases - Chengzhi Li; Huimin You; Hong Zhang; Yulong Liu; Wanghai Li; Xiaobai Wang; Yan Zhang (PeerJ, 2019)
Objective This study aimed to introduce and evaluate the safety and efficacy of the relay puncture technique in patients with complicated lower extremity arterial diseases. Methods A total of 21 patients (16 male and five female patients; median age: 68.5 years old), who had suffered from lower extremity arterial diseases between December 2014 and July 2017, were retrospectively collected. For all patients, the contralateral femoral artery was not available for puncture access, and the length of the devices was too short for the brachial artery approach. Therefore, the relay puncture technique, in which the first puncture was performed on the brachial artery, followed by an antegrade puncture on the femoral artery, was used to accomplish the endovascular therapy. Percutaneous transluminal angioplasty and/or percutaneous transluminal stenting were/was used to assess the efficacy of the relay puncture technique. The ankle–brachial index (ABI) and Rutherford clinical classification were used to evaluate the improvement of symptoms after treatment. Patients were followed up for 1, 3, 6, and 12 months, and annually (mean: 16.6 months) after discharge. Results The relay puncture treatment had a 100% technical success rate, and immediately decreased the ischemic symptoms of patients after the procedure. The ABI significantly increased from 0.33 ± 0.18 to 0.75 ± 0.21 at the 1-year follow-up time point (P < 0.05). No serious complications occurred during the follow-up period. The 1-year primary patency rate was 71.43%. Conclusion The relay puncture technique is a feasible technique in the hands of experienced and skilled equipment operators for the treatment of lower extremity arterial diseases, when the contralateral femoral artery is not available for puncture, and the length of the device is too short to treat the distal lesion of the femoral artery and popliteal artery through the brachial artery approach.